Challenges and lessons learned for institutional review board procedures during the COVID-19 pandemic. Issue 1 (16th March 2021) - Ford, Daniel E.; Johnson, Ann; Nichols, Jason J.; Rothwell, Erin; Dubinett, Steve; Naeim, Arash
Abstract: The COVID-19 pandemic changed the clinical research landscape in America. The most urgent challenge has been to rapidly review protocols submitted by investigators that were designed to learn more about or intervene in COVID-19. International Review Board (IRB) offices developed plans to rapidly review protocols related to the COVID-19 pandemic. An online survey was conducted with the IRB Directors at Clinical and Translational Science Awards (CTSA) institutions as well as two focus groups. Across the CTSA institutions, 66% reviewed COVID-19 protocols across all their IRB committees, 22% assigned protocols to just one committee, and 10% created a new committee for COVID-19 protocols. Fifty-two percent reported COVID-19 protocols were reviewed much faster, 41% somewhat faster, and 7% at the same speed as other protocols. Three percent reported that the COVID-19 protocols were reviewed with much better quality, 32% reported slightly better quality, and 65% reported the reviews were of the same quality as similar protocols before the COVID-19 pandemic. IRBs were able to respond to the emergent demand for reviewing COVID-19 protocols. Most of the increased review capacity was due to extra effort by IRB staff and members and not changes that will be easily implemented across all research going forward.